Mesostructured Catalysts Based on the BEA Topology for Olefin Oligomerisation. Issue 13 (26th January 2018) - Silva, Andreia F.; Fernandes, Auguste; Neves, Patrícia; Antunes, Margarida M.; Rocha, Sílvia M.; Ribeiro, Maria F.; Silva, Carlos M.; Valente, Anabela A.
Abstract: Mesostructured solid acid catalysts based on the BEA topology were explored for olefin oligomerisation, which is an attractive synthetic route to produce clean, sulfur‐free fuels or fuel additives with reduced aromatics content. Specifically, the oligomerisation of 1‐butene, which may derive from (non‐)renewable sources, was performed under high pressure and continuous‐flow operation. The mesostructured catalysts consisted of a hierarchical zeotype (BEA‐hier) synthesized by a one‐pot approach using a dual‐function template and, on the other hand, a composite (BEA/TUD) possessing zeolite nanocrystallites embedded in a mesoporous matrix synthesised under hydrothermal conditions. The influence of the material properties, catalyst activation temperature and reaction parameters were investigated by combining characterisation, two‐dimensional gas chromatography combined with time‐of‐flight mass spectrometry (ToFMS) studies, and catalytic studies. The catalytic performances were compared to those of commercial nano/microcrystalline zeolites of different topologies and COD‐900 (type of catalyst for the conversion of olefins to distillates process). BEA‐hier performed superiorly in terms of conversion and space–time yields to diesel cut products. Abstract : Optimized zeolite=zeotype ! Oligomerization of butene, derivable from (non)renewable sources, is an attractive synthetic route to produce clean fuels. Comparisons with commercial zeolites and COD‐900 show that a mesostructured zeotype possessing BEA topology performs superiorly in terms of catalytic conversion and space–time yield (STY) to C10+ products.